Utilization of dried saluyot powder in baked products - Perez, Dulcinea Laarni K.; Galvez, Flor Crisanta F. (1995.)
The effects blanching time (2, 4, and 6 minutes) and drying temperature (60, 70, and 80°C) on the beta-carotene content of dried saluyot powder were determined. Dried saluyot powder was prepared at optimum blanching time and drying temperature and utilized in the preparation of brownies at different levels of substitution of the wheat flour (0-50% at 10% increments). The effect on the consumer acceptance of the sensory characteristics of the brownies was investigated using the 24 consumer panelists and 9-point scales. Maximum retention of beta-carotene (0.117% w/w) was obtained when blanching was done for 4 minutes with subsequent drying of the saluyot leaves at 80°C. Increased levels of substitution of wheat flour with dried powder significantly improved the color of brownies but did not affect the texture and flavor. Overall acceptability of the brownies by consumers increased as the amount of saluyot powder used increased.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Vegetables -- Philippines; Saluyot